Evaluation of Tuberculosis Surveillance System in North Sumatra Provincial Health Office 2022 - Novia Syahreni; Muhammad Atoillah Isfandiari; Frans Yosep Sitepu (RIRAI Publisher, 2023)
Tuberculosis Global Report 2021 TB was being the major death caused by one infection agent. Result of health problem analysis in North Sumatra Provincial Health Office, TB was choosen as the first priority with main determinant low treatment coverage TB. The purpose of this study is to know the implementation of surveillance TB system based on system approach and evaluate based on surveillance attribute in North Sumatra Provincial Health Office 2022. The type of research is descriptive with evaluation design. Subject of the research was surveillance TB system has been implemented in North Sumatra and Deli Serdang Health Office District in 2021 with TB officer in Health Office. Data collected by interview with TB officer using questionarre and supported by document study. Evaluation was doing by system approach and based on surveillance attribute. The data interpreted by narration and table. Results of evaluation system component TB in Health Office in Provincial and District obtained that implementation system of TB was appropriate with surveillance guidelines and TB control guidelines by Ministry of Health. Based on attribute evaluation, from 9 attributes Health Office Provincial and Distrcit got 5 attributes with good results means that TB surveillance program was simple, acceptable, good data quality, sensitive, and stable but the surveillance program was not flexible, low predictive value positive, not timeliness, and not representative. Based on the evaluation results, TB surveillance system in North Sumatra Provincial Health Office and Deli Serdang District Health Office has a good system based on input, process, and output. Based on attribute surveillance, its still need some improvements in terms of increasing predictive value positive by doing screening people before TCM examination and analysis of cases by person place and time so the data would be representative and describe the real condition